Josephus and the politics of historiography : apologetic and impression management in the Bellum Judaicum - Mader, Gottfried (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2000)
A study of the "Bellum Judaicum". It reconsiders Josephus' intellectual affiliation to his predecessors and argues that the work's classical complexion, and in particular its distinctive "color Thucydides", are integral to its intellectual and ideological design.